Juridical Review of Replacement Certificates of Land Rights Due to Loss at the Medan City Land Office - Hutagalung, Yuni Mifta Afida; Falahiyati, Nurhimmi; Ahmad, Akiruddin (Inovasi Pratama Internasional. Ltd, 2024)
An application for a replacement certificate can only be made by the party whose name appears as the right holder in the land book at the local land office. An application for a replacement certificate cannot be made if the name of the party is different from the name of the right holder in the land book. If the right holder listed in the land book has died, the application can be made by his heirs. The application must be accompanied by valid supporting documents, such as a Certificate of Death from the right holder and a Certificate of Heirs and Heirs. The formulation of the problem in this research is How is the Procedure for the Implementation of the Issuance of Land Rights Substitute Certificates at the Medan City Land Office. How are the obstacles and efforts faced by the Medan City Land Office in the Implementation of the Issuance of Replacement Certificates of Land Rights that are lost. The type of research used in this research is juridical-empirical. Juridical-empirical research is legal research on the enactment or implementation of normative legal provisions directly on each specific legal event that occurs in society. An application for a replacement certificate due to loss can only be submitted by the party whose name is listed as the right holder in the relevant land book or another party who is the recipient of the right based on a PPAT deed or an excerpt of minutes of auction, deed, letter and power of attorney. If the right holder or beneficiary has died, an application for a replacement certificate can be submitted by his heirs by submitting a letter of proof as an heir.